Identification of Genes Preferentially Expressed in Stomatal Guard Cells of Arabidopsis thaliana and Involvement of the Aluminum-Activated Malate Transporter 6 Vacuolar Malate Channel in Stomatal Opening - Ye, Wenxiu; Koya, Shota; Hayashi, Yuki; Jiang, Huimin; Oishi, Takaya; Kato, Kyohei; Fukatsu, Kohei; Kinoshita, Toshinori (Frontiers in Plant Science, 2021)
Stomatal guard cells are highly specialised cells that respond to various stimuli, including blue light and abscisic acid, for regulation of stomatal aperture. Many signaling components involved in stomatal movement have been shown to be preferentially expressed in guard cells. Here, we identified four new such genes in addition to an aluminium-activated malate transporter, ALMT6, and GDSL lipase, Occlusion of Stomatal Pore 1 (OSP1), based on expression analysis using public resources, reverse transcription-PCR, and promoter-driven β-glucuronidase assays. Some null mutants of guard cell-specific genes evidenced altered stomatal movement. We further investigated the role played by ALMT6, a vacuolar malate channel, in stomatal opening. Epidermal strips from an ALMT6-null mutant exhibited defective stomatal opening induced by blue light and fusicoccin, a strong plasma membrane H+-ATPase activator. The deficiency was enhanced when the assay buffer [Cl-] was low, suggesting that malate and/or Cl- facilitate efficient opening. The results indicate that guard cell-specific genes are frequently involved in stomatal movement. Further detailed analyses of the hitherto uncharacterised guard cell-specific genes will provide new insights into stomatal regulation.